Long non‐coding RNA lnc‐PCTST predicts prognosis through inhibiting progression of pancreatic cancer by downregulation of TACC‐3. Issue 12 (15th November 2018) - Wang, Yandong; Ding, Xiangya; Hu, Hao; He, Yuan; Lu, Zipeng; Wu, Pengfei; Tian, Lei; Xia, Tianfang; Yin, Jie; Yuan, Hao; Shi, Guodong; Liu, Dongfang; et al.
Abstract : Pancreatic cancer (PC), which is one of the most lethal of malignancies and a major health burden, is associated with a dismal prognosis despite current therapeutic advances. Numerous long noncoding RNAs (lncRNA) have shown to be essential for PC tumorigenesis and progression. Nevertheless, the exact expression pattern of lnc‐PCTST and its clinical significance still remain unclear. This study investigates the expression pattern of lnc‐PCTST and its associated mRNA in three paired PC tissues and adjacent non‐tumor tissues by Microarray‐coarray approach. Briefly, our data demonstrated that lnc‐PCTST expression is down‐regulated in PC tissues. Also, lnc‐PCTST has shown to be negatively correlated with transforming acidic coiled‐coil 3 (TACC‐3) expression. This expression pattern was further confirmed following qRT‐PCR validation of 34 out of 48 paired cancer tissues. Furthermore, lnc‐PCTST overexpression in PC cell lines inhibited cell proliferation and invasion in vitro, and tumorigenesis in vivo (using nude mice as animal model), but did not altered cell migration. Moreover, lnc‐PCTST overexpression increased E‐cadherin and repressed vimentin expression in vitro . Additionally, TACC‐3 knockdown simulated the inhibiting effect of lnc‐PCTST overexpression on PC cell lines, and the impaired proliferation, invasion effect and E‐cadherin, vimentin expression on lnc‐PCTST over‐expressed cell lines can be rescued by overexpressed TACC‐3. Significantly, the expression of lnc‐PCTST was closely associated with its genomic neighboring gene TACC‐3 and inhibited its promoter activity. In conclusion, lnc‐PCTST is a potential tumor suppressor in PC, which inhibits cell proliferation, invasion, tumorigenesis and EMT by modulating TACC‐3. Abstract : What's new? Numerous long noncoding RNAs (lncRNAs) have shown to be essential in pancreatic cancer (PC) tumorigenesis and progression. Nevertheless, the exact expression pattern of lnc‐PCTST and its clinical significance remain unclear. Here, the authors investigated the expression pattern of lnc‐PCTST and its associated mRNA in three paired PC tissues and adjacent non‐tumor tissues. A low expression of lnc‐PCTST was found in pancreatic cancer tissues. Furthermore, multivariate analysis indicated that lnc‐PCTST expression and tumor size were key independent prognostic factors. Finally, in vivo and in vitro experiments showed that lnc‐PCTST suppressed PC progression and epithelial mesenchymal transition‐induced invasion through downregulation of TACC‐3.